Assimilation patterns in cities - Yasuhiro Sato; Yves Zenou (Research Institute of Industrial Economics (IFN), 2019)
We develop a model in which ethnic minorities can either assimilate to the majority's norm or reject it by trading off higher productivity and wages with a greater social distance to their culture of origin. We show that "oppositional" ethnic minorities reside in more segregated areas, have worse outcomes (in terms of income) but are not necessarily worse off in terms of welfare than assimilated ethnic minorities who live in less segregated areas. We find that a policy that reduces transportation cost decreases rather than increases assimilation in cities. We also find that when there are more productivity spillovers between the two groups, ethnic minorities are more likely not to assimilate and to reject the majority's norm. Finally, we show that ethnic minorities tend to assimilate more in bigger and more expensive cities.
Keywords: J15; R14; Z13; 330; Identity; Agglomeration economies; Cities; Ethnic minorities; Welfare